Molecular Signatures of End-Stage Heart Failure - Lin, David; Hollander, Zsuzsanna; Meredith, Anna; Stadnick, Ellamae; Sasaki, Mayu; Cohen Freue, Gabriela; Qasimi, Pooran; Mui, Alice; Ng, Raymond T.; Balshaw, Robert; Wilson-McManus, Janet E.; Wishart, David; et al. (Journal of cardiac failure, 2011)
To date, gene expression studies related to chronic heart failure (CHF) have mainly involved microarray analysis of myocardial tissues. The potential utility of blood to infer the etiology, pathogenesis, and course of CHF remains unclear. Further, the use of proteomic and metabolomic platforms for molecular profiling of CHF is relatively unexplored. Microarray genomic, iTRAQ proteomic, and nuclear magnetic resonance metabolomic analyses were carried out on blood samples from 29 end-stage CHF patients (16 ischemic heart disease [IHD], 13 nonischemic cardiomyopathy [NICM]), and 20 normal cardiac function (NCF) controls. Robust statistical tests and bioinformatical tools were applied to identify and compare the molecular signatures among these subject groups. No genes or proteins, and only two metabolites, were differentially expressed between IHD and NICM patients at end stage. However, CHF versus NCF comparison revealed differential expression of 7,426 probe sets, 71 proteins, and 8 metabolites. Functional enrichment analyses of the CHF versus NCF results revealed several in-common biological themes and potential mechanisms underlying advanced heart failure. Multiple “-omic” analyses support the convergence of dramatic changes in molecular processes underlying IHD and NICM at end stage.